Penggunaan Performance Sebagai Pemoderasi: antara Pengungkapan Corporate Social Responsibility, Kepemilikan Keluarga dan Beban Research and Development Terhadap Tax Avoidance - Yohanes August Goenawan; Dadan Ramdhani; Christien Setiya Kesumawati; Raden Willi Fatimaleha (STATERA: Jurnal Akuntansi dan Keuangan, 2021)
This study aims to analyze the effect of corporate social responsibility disclosure, family ownership and research and development expense on tax avoidance with performance as moderating variable. The population of this research is consumer goods companies listed on Indonesia Stock Exchange in 2014- 2018. The samples tested in this study were 15 companies taken based on the purposive sampling method. The data used in this study are secondary data from annual reports and financial reports. This study used multiple linear regression analysis and moderated regression analysis. The results of this research showed that the variable corporate social responsibility had a negative and significant influence on tax avoidance, meanwhile family ownership and research and development expense had not significant influence on tax avoidance. Also, performance can strengthened the effect of family ownership and research and development expense on tax avoidance, meanwhile corporate social responsibility can not be moderated.